ANALISIS RASIO LIKUDITAS AKTIVITAS DAN PERTUMBUHAN LABA PADA KSP KARYA ABADI - Asmarani Tasik Madika; Ahmad Tomu (JURNAL ULET (Utility, Earning and Tax), 2022)
This study aims to determine the level of liquidity, effectiveness of working capital and the rate of profit growth at KSP Karya Abadi by using financial ratio analysis, namely the ratio of liquidity, activity and profit growth. This research was carried out in Mimika Regency, precisely at the KSP Karya Abadi which is located on Leo Mamiri Street. The results of the study show that the company's financial performance is not good because it is still below the average financial ratio.